Study of diamond-like carbon films doped with transition metals and used as cathodes for current creation in water - Primachenko, V.E.; Lukjanov, A.N.; Kirillova, S.I.; Chernobay, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Properties of diamond-like carbon films (DLCF) on n-Si substrates used as
cathodes in Yb – DLCF (n-Si) water electrochemical system have been studied by
current creation with water decomposition H2O → OH⁻
+ H⁺
. The current is several
times higher after preliminary electrolytic deposition of impurity that contains one of the
transition metals (Pd, Pt, Ni, Cr) on DLCF (n-Si) layer, which changes the nature of the
catalytic process of water decomposition. The aging effect of DLCF (n-Si) 〈Me〉 was
observed after 7- to 25-day metal oxidation in air. It is confirmed the change of the
electron work function of CDL (n-Si) 〈Me〉 electrode and the current change between it
and the Yb electrode.